PERFORMANCE ANALYSIS AND MODELING OF PASSENGER PUBLIC TRANSPORT SERVICES IN SALATIGA CITY - Handajani, Mudjiastuti; Firmawan, Ferry; Harmini, Harmini (ASTONJADRO, 2021)
The performance condition of public transportation services in Salatiga City does have an average rating of still good, but it still has classic problems such as there is no passenger stop, public transportation takes a long time to catch up on deposits, and passengers do not know the fare per kilometer that must be paid. These conditions encourage research activities in the form of an analysis of the performance of public transport passengers in Salatiga City (Case Study of the Tamansari – Blotongan Route). The long-term goal of this research is that the resulting analysis can contribute to stakeholders in Salatiga City, especially in terms of (public transport) towards smart transportation. The specific target to be achieved from the research is the analysis and modeling of the performance of passenger public transport services that will be carried out in Salatiga City, in the form of field surveys and secondary data collection, namely: number of vehicles, number of passengers and data in the form of public transport routes: routes, schedules, speeds and Primary forms are: boarding alighting (up and down passengers) and headway (distance between two public transport vehicles). The analytical method used is the analysis and modeling of the performance of passenger public transportation services in accordance with Government Regulation No. 10 of 2012 Directorate General of Land Transportation concerning Minimum Service Standards for Road-Based Mass Transportation. The results showed that the physical condition of the passenger fleet of Salatiga City on the Tamansari - Blotongan PP route was classified as suitable for use. There are a total of 90 fleets that are sufficient for the needs of Salatiga City public transport passengers who want to travel by means of transportation. The results of the performance analysis based on various indicators show that the performance quality of public transportation services in Salatiga City has met the standards set by the Directorate General of Land Transportation. It can be seen from the results of the load factor analysis with a value of 0.72, the value is included in category A, namely > 0.8. For the level of satisfaction and level of performance, most of the indicators have met the satisfaction of public transport passengers in Salatiga City, so it is sufficient to maintain it. However, there are indicators of waiting times for public transportation that need to be improved.